The killing of a sacred deer [videorecording (DVD)] - Lanthimos, Yorgos, 1973-; Farrell, Colin, 1976-; Kidman, Nicole, 1967-; Keoghan, Barry, 1992- (Lions Gate Entertainment, 2018)
Steven, a charismatic surgeon, is forced to make an unthinkable sacrifice after his life starts to fall apart, when the behavior of a teenage boy he has taken under his wing turns sinister.